PEMANFAATAN MEDIA LECTURE MAKER DALAM PEMBELAJARAN KIMIA MELALUI PENERAPAN PROFESSIONAL LEARNING COMMUNITY DI SMA NEGERI 1 BATANG ANGKOLA - Heni Mulyani Pohan; Fatma Suryani Harahap; Elisa Elisa; Alfiansyah Halomoan Siregar; Fitri Agustina Lubis; Paisal Hamid Marpaung (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2023)
This study aims : (1) Wheather the Lecture Maker can improve student  chemistry learning outcomes on the subject Mekanika Kuantum in the class XI IPA SMA Negeri 1 Batang Angkola. (2) Difference in direct learning  models by utilizing  Lecturer Maker media through the application of Proffesional Learning Community than direct teaching method without use of Lecture Maker media compare to direct learning models without utilizing  Lecture Maker media on student chemistry learning outcomes. The kind of this study is experiment, XI IPA 4 as the experiment class and XI IPA 3 as the control class. Data on learning outcomes are taken using tests. Before the test given to the student is first tested for feasibility outside the sample, including validity test, reliability test, differentiability and difficulty of the test. Data analysis techniques use normality tests, homogeneity tests, and hypothesis testing. Analysis result show the study result in the experiment class is average 63,39 to 76,42 increased 13,03. While the study result in the control class is average 50,52 to 59,73 increased 9,21. The percentage study result in the experiment class with use of Lecture Maker media through Proffesional Learning Community 30,12% be 49,34% increased 19,22%. Based on the control class without use Lecture Maker the percentage is 21,26% be 35,87% increased 14,61%. Based on the result show thitung > ttabel so H0 ignored and Ha accepted. Hypothesis 1 is accepted. Can be seen average experiment class higher 76,62 than average control class 59,73 so H0 ignored and Ha accepted. So the hypothesis 2 can accepted too.